2007
DOI: 10.1117/1.2750287
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating basal cell carcinoma from perilesional skin using high wave-number Raman spectroscopy

Abstract: An expanding body of literature suggests Raman spectroscopy is a promising tool for skin cancer diagnosis and in-vivo tumor border demarcation. The development of an in-vivo diagnostic tool is, however, hampered by the fact that construction of fiber optic probes suitable for Raman spectroscopy in the so-called fingerprint region is complicated. In contrast, the use of the high wave-number region allows for fiber optic probes with a very simple design. We investigate whether high wave-number Raman spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 36 publications
6
121
1
Order By: Relevance
“…This strong signal is often exploited for rapid CARS imaging [130]. High wavenumber bands from proteins can sometimes be seen, but nucleic acid signals are too weak to be detected [130,131]. Water also exhibits broad, overlapping intramolecular O-H stretching contributions in the 3000-3700 cm −1 region.…”
Section: High Wavenumber Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strong signal is often exploited for rapid CARS imaging [130]. High wavenumber bands from proteins can sometimes be seen, but nucleic acid signals are too weak to be detected [130,131]. Water also exhibits broad, overlapping intramolecular O-H stretching contributions in the 3000-3700 cm −1 region.…”
Section: High Wavenumber Regionmentioning
confidence: 99%
“…They found that the Raman signal from the high wavenumber region contained similar information and could create similar hyperspectral images to those from specta in the fingerprint region [436]. They used this high wavenumber Raman probe to classify different types of brain tissue [129] and distinguish between basal cell carcinoma and other skin conditions [131].…”
Section: Challengesmentioning
confidence: 99%
“…For example, a traditional Fourier-transform Raman system requires up to 30 minutes of integration time to acquire one spectrum. Most prior studies involving the skin have been limited to either ex vivo samples or a few in vivo skin measurements, all requiring relatively long integration times (9)(10)(11)(12)(13)(14). The clinical use of ex vivo Raman spectroscopy is quite limited, as suspect lesions must first be biopsied, which necessarily entails an invasive procedure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for a wide variety of applications including cancer diagnosis [1,2], the detection of hazardous materials [3], and industrial quality control. Raman spectroscopy has previously been carried out in turbid media [4,5]; however, the effect elastic scattering has on the process has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%